Exploring Post-stroke Epilepsy from the Doctrine of Constitution in Chinese Medicine - Peng, Menghan; Ling, Zhang (Journal of Contemporary Medical Practice, 2024)
The incidence of stroke disease is high in current society, and there are many secondary complications. Post-stroke epilepsy (PSE) is one of the common complications, which is considered to be the most common symptomatic epilepsy and intractable neurological disease in the elderly. According to related literature, the occurrence of post-stroke epilepsy is related to TCM somatics to a certain extent. Therefore, this study investigates the distribution pattern of post-stroke epilepsy and TCM somatics and analyzes the correlation of its influencing factors, so as to provide new methods and ideas for the prevention and treatment of post-stroke epilepsy by using theories related to TCM somatics to intervene in the early stage of post-stroke epilepsy and to reduce the incidence rate.